The Kurds in Erdoğan's Turkey balancing identity, resistance and citizenship - Gourlay, William (Edinburgh studies on modern Turkey., 2020)
This book examines the circumstances of the Kurds in 21st century Turkey, under the hegemony of the AKP government. After decades of denial, oppression and conflict, Kurds now assert a more confident presence in Turkey's politics -- but does increasing visibility mean a rejection of Turkey? Recording Kurdish voices from Istanbul and Diyarbakır, Turkey's most important Kurdish-populated cities, this book generates new understandings of Kurdish identity and political aspirations. Highlighting elements of Kurdish identity including Newroz, the Kurdish language, connections to religion, landscape and cross-border ties, it offers a portrait of Kurdish political life in a Turkey increasingly dominated by its president, Recep Tayyip Erdoğan. Within the context of Turkey's troubled trajectory towards democratisation, it documents Kurdish narratives of oppression and resistance, and enquires how Kurds reconcile their distinct ethnic identity and citizenship in modern Turkey.--